Diversity and Challenges of Industrial peace in Work Place in Nigeria - Adigun, Abel. O. (Advances in Social Sciences Research Journal, 2017)
The work place is very diverse and this leads to conflict or absence of industrial peace. The Nigerian conditions in its peculiarities exacerbate conflict in industry and government policies developed to deal with these conflicts have not been effective. This paper centers on the search for industrial peace in industry in Nigeria especially in the increasing unitarist policies seen in industry today. Many businesses disregard welfare, diversity and humanistic principles in dealing with the employees. They deny the employees basic rights that come with working in industry. This fact makes conflict the order of the day in industry in Nigeria. This paper submits, using critical analysis, that organizations within industries should create enabling environment for effective industrial relations’ activities to thrive by assisting it where necessary so as to stabilize the organization and bringing about peace. Effective industrial relations must necessarily adopt humanistic principles and sound human resource department in order to achieve peace.